Evaluasi Dampak Kebijakan Bantuan Peralatan Pengolahan Pada Produksi Kerupuk Ikan Di Kecamatan Jongkong Kabupaten Kapuas Hulu - Hermiwati Hermiwati (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2020)
AbstractThis research aims to describe and analyze the policy impact of providing assistance for processing fish dracker production equipment to the processing community gruoup in Jongkon Sub-District, apuas Hulu Regency. From research results conducted on the fishery product prodessing group in Jongkong Sub-District, It is indicated that the provision for fishery prodessing equipment assistance has positive impacts on indreasing product volume and prodessor income (group). In terms of effectiveness, there is a difference between yield volume and processing income from before and after assistance. In terms of efficiency, the assistance can save labor, speed up the processing process so as to increase income. The assistance fulfills the adequacy criteria because it can solve the quality problem of the processed products and is deemed adequate because the assistance is in the form of a complete package so that it is highly appreciated by the processor. The assistance meets the leveling criteria as itu can be seen that all group members in the group receive the same assistance, while other groups are given in turn. Responsiveness can also be fulfilled because respondents said that the assistance is appropriate and in accordance with their needs and the equipment is used optimally. The accuracy criteria of this program can be seen that the assistance of equipment that will be very much in line with the mprovement of product quality. This will increase the competiveness and expansion of marketing. Therefore, it gives a positive value and can be recommended to be continued in the coming years. Key words : Impact Evaluation, Fish Crackers, Jongkong Sub-District, that the Kapuas Hulu Regency